Developing and evaluating management zones for variable rate fertilizer application - Fleming, Kim L., author; Westfall, Dwayne G., advisor (Colorado State University. Libraries, 2003)
Variable rate fertilizer application technology (VRT) can provide an opportunity to more efficiently utilize N fertilizer inputs, however accurate prescription maps are essential. Grid soil sampling has most frequently been used to develop these prescription maps. Research has shown this method has several technical and economic limitations. Defining management zones that characterize the spatial variability within a field may provide for a more effective use of VRT. Management zones can be defined as spatially homogeneous sub-regions within a field that have similar crop input needs The initial objective of this dissertation was to evaluate management zones identified using soil color from aerial photographs and farmer experience. These farmer developed management zones were compared to soil nutrient levels, texture, apparent soil electrical conductivity readings, topography, and crop yields collected in 1997,1998, 1999, and 2000 at two fields. Analysis indicates that this method can be useful in identifying different management zones. The soil and yield parameters followed the trends indicated by the management zones at field one with the highest values found in the high productivity zones and the lowest the low productivity zones. Significant differences were found among the management zones. At field two the low productivity zone was significantly lower in the soil and crop parameters, however high and medium productivity zones were generally not significantly different. Further testing over a broader scope of fields and crop production systems can follow to confirm these results. A second objective was to evaluate and compare the prescription maps using the management zones described above with prescription maps developed from grid soil sampling. To achieve this objective six N treatments were applied on three center pivot irrigated corn fields in northeast Colorado in 1999 and 2000. There were no significant differences in yield between the treatments developed from management zones and the treatments developed from grid soil sampling. These data indicate that management zone based variable rate application is at least equally effective as grid based application. However, the cost of implementing the management zone based VRT program is much less making it a profitable alternative to grid soil sampling. The final objective for the dissertation was to compare and evaluate prescription maps developed from soil color and farmer experience with prescription maps developed from apparent soil electrical conductivity. Apparent soil electrical conductivity (ECa) has proven to relate closely to other properties that often determine a field's productivity. Management zones based on ECa were developed on two fields using a GPS equipped Veris® model 3100 conductivity sensor. These two methods of developing management zones were compared to soil nutrient levels, texture, and crop yields collected in 1997 and 1998. The soil and yield parameters followed the trends indicated by both management zone methods at field 1 with the highest values found in the high productivity zones and the lowest the low productivity zones. Significant differences were found among the management zones. However at field two the high and medium productivity zones were not significantly different using the soil color approach while the soil conductivity approach was effective in identifying three distinct management zones. Both methods of developing management zones seem to be identifying homogeneous subregions within fields. Matching crop inputs to the variability that occurs in farm fields using precision farming technologies appears to have the potential to increase cropping efficiency. However, choosing the most effective methods to utilize these technologies is key in obtaining the benefits they may provide.
Keywords: agronomy; soil sciences